Spectral Investigation of Complex Ion Formation in Cu-Co-Ni-Halide with Alkali Halides - N. Modi, Ashvin; Patel, Dinesh; Desai, C.M. (Asian Journal of Chemistry, 2010)
Spectral absorbance of nickel chloride, cobalt chloride or cupric chloridewith alkali chloride systems was studied by dye indicators (i.e., crystalviolet (C.V.), and methylene blue (M.B.)) showing corresponding complexion formation in ratio of 1 : 2, 1: 1 and 2: 1.